Constitutional psychic human qualities influence on the emotional and psychic state at the patients with neurological spine disorders - Nazarchuk, Iryna A. (Psychiatry, Neurology and Medical Psychology, 2021)
Objective - to study the emotional and psychic state at the patients with neurological cervical spine disorders (NCSD) and determine of the constitutional psychic human qualities influence at the it.  Methods and subjects. 87 patients (18-44 years old), who suffered from subacute and chronic NCSD, were examined by clinical-anamnestic, clinical-functional (vertebral neurological), clinical-neurological methods. Emotional and psychic state was examined by Spielberger-Hanin test and Hamilton Depression Rating Scale. Psychic functions of human constitution were studied by temperament type determining with using Eysenck’s EPQ questionnaire.Results and discussion. The course of subacute and chronic cervicalgia, cervicocranialgia, cervicobrachialgia (neck and shoulder pain) was characterized depression symptoms at the melancholic temperament type (at 76% patients, р< 0,05). At the choleric temperament type depression symptoms was present meeted very often too (at 68% patients). At the sanguine temperament type depression symptoms was very rarely (at 29% patients). The peculiarities from reactive and personality anxiety were found too. It were at the melancholic and choleric patient highter significantly, than at the sanguine patients (p <0,05, p <0,01, p < 0,001). Temperament influence on the depression symptoms and anxiety confirmed by reliable correlations.Conclusions. The emotional and psychic state at the patients with NCSD characterize as anxiety on the background of neurological symptoms of cervicalgia, cervicocranialgia, cervicobrachialgia (neck and shoulder pain).  It this symptoms add with decreased performance, mood and sleep disturbances and all these complaints in the aggregate are summed up as depressive disorders, mainly of mild severity. Constitutional psychic human qualities, which included in temperament, influence on the it formation. The models of influence different temperament types on the emotional and psychic states at the patients with NCSD were represented. It points pathogenic significance of melancholic and choleric temperament types and sanogenetic qualities of sanguine type. Constitutional psychic human qualities and emotional and psychic state should be considere at the diagnostic and treatment patients with NCSD.  Significance of the human constitution, emotional and psychic state for NCSD confirm by study results. It is background for following studies.